Participación del sistema endocannabinoide de la interfaz maternofetal en el inicio del parto a término y pretérmino - Marvaldi, Carolina (2024)
Preterm birth (PTB) is a multifactorial syndrome and the leading cause of morbimortality in children under the age of 5. The endocannabinoid system (ECS) is a complex lipid signaling pathway composed of a plethora of fatty acids-derived mediators, their receptors, and metabolic enzymes. This system is involved in several aspects of reproductive physiology, including fertilization and childbirth. An imbalance in the components of ECS can lead to adverse pregnancy outcomes such as preterm birth. The decidua is a transitory organ that is formed during pregnancy from the endometrium and is essential to preparing, establishing and maintaining pregnancy. Furthermore, this organ has a high influx of infiltrating cells. For this reason, the aim of this work was to study the role of the endocannabinoid system from deciduas and peripheral blood mononuclear cells (PBMC) in the molecular processes involved in the triggering of preterm birth.\nIn this work, we demonstrated the presence of the main components of ECS in decidua and PBMC from mice on day 15 of gestation, and the treatment with an inflammatory agent like lipopolysaccharide (LPS) modulates these components. On the other hand, we demonstrated that the deletion of the gene encoding CB1 receptor (the main cannabinoid receptor) confers protection to the pregnant mother against an inflammatory challenge. We used a murine model of inflammation during pregnancy, induced by the systemic administration of LPS, where we observed that CB1-KO females present a lower rate of PTB than WT females. Furthermore, CB1-KO deciduas showed lower enzymatic activity of the main endocannabinoid?s degradation enzyme (FAAH). In these deciduas, we demonstrated that anandamide (AEA, main endocannabinoid) remains stable when challenged with LPS. However, we observed an increase in AEA levels in deciduas from WT females after LPS treatment. In serum from pregnant mice, the same AEA pattern is observed.\nUsing this model of PTB, we investigated the mechanisms associated with the triggering of labor. We found that CB1-KO mice present lower levels of prostaglandins and metalloproteases in deciduas after LPS treatment in comparison with WT.\nOn the other hand, to corroborate the results obtained in CB1-KO mice, we used a pharmacological approach. We cultured control deciduas and incubated them with LPS and cannabinoids receptors? antagonists. The co-treatment with LPS and AM251 (CB1 antagonist) did not modify COX-2 protein levels in comparison with LPS, however the co-treatment with LPS and AM251 prevented the increase of prostaglandin levels, in the same way as in the animal model.\nWe concluded that the blockade of CB1 receptor protects the mother against the induction of PTB mediated by LPS. This result confirms that ECS of the decidua is involved in the mechanisms prior to the onset of preterm labor. The ECS is responsible for mediating the biological effects of cannabis, the most frequently used recreational drug in reproductive age population worldwide. Hence, the results obtained in this work contribute to the discussion on the safety of cannabis consumption during pregnancy.\nFurthermore, ECS could be postulated as a possible non-invasive biomarker that allows anticipating the threat of preterm birth. This could lead to the design of new strategies to prevent premature delivery.